2022
DOI: 10.1177/10298649221110089
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese translation of the Gold-MSI: Adaptation and validation of the self-report questionnaire of musical sophistication

Abstract: This study presents a Japanese translation of the Goldsmiths Musical Sophistication Index (Gold-MSI). The index consists of 38 self-report questions and provides a general sophistication score as well as subscale scores for Active Engagement, Perceptual Abilities, Musical Training, Singing Abilities, and Emotions. The validation of the translation with 689 native Japanese speakers indicated excellent internal consistency and test–retest reliability. Confirmatory factor analysis revealed that the bifactor model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…All participants confirmed that they knew the four familiar melodies used in the experiment. The participants’ musical ability was evaluated using the Japanese Gold-MSI questionnaire 51 (the original is Müllensiefen et al 52 ), which evaluates General Sophistication ( M = 62.5, SD = 18.0) as well as subscales of Active Engagement ( M = 30.0, SD = 8.3), Perceptual Abilities ( M = 38.7, SD = 10.4), Musical Training ( M = 20.9, SD = 10.2), Emotions ( M = 29.1, SD = 7.3), and Singing Abilities ( M = 24.3, SD = 8.7). Four participants had self-reported absolute pitch.…”
Section: Methodsmentioning
confidence: 99%
“…All participants confirmed that they knew the four familiar melodies used in the experiment. The participants’ musical ability was evaluated using the Japanese Gold-MSI questionnaire 51 (the original is Müllensiefen et al 52 ), which evaluates General Sophistication ( M = 62.5, SD = 18.0) as well as subscales of Active Engagement ( M = 30.0, SD = 8.3), Perceptual Abilities ( M = 38.7, SD = 10.4), Musical Training ( M = 20.9, SD = 10.2), Emotions ( M = 29.1, SD = 7.3), and Singing Abilities ( M = 24.3, SD = 8.7). Four participants had self-reported absolute pitch.…”
Section: Methodsmentioning
confidence: 99%
“… Note: n = number of items. Cronbach’s α values are derived from: en = English (Müllensiefen et al, 2014, N = 147,633), de = German (Schaal et al, 2014, N = 641), pt = Portuguese (Lima et al, 2020, N = 408), fr = French (Degrave & Dedonder, 2019, N = 750), zh-TW = Traditional Chinese (Lin et al, 2021, N = 1108), ja = Japanese (Sadakata et al, 2022, N = 689). …”
Section: Methodsmentioning
confidence: 99%
“…Compared to other measurement tools developed in recent years, the Goldsmith’s Musical Sophistication Index (Gold-MSI, Müllensiefen et al, 2014) is unique in that it is for those who are not necessarily musically trained, which means it allows for the capture and analysis of individual differences in musical sophistication across a broader spectrum. Furthermore, it has been translated into several languages, including German (Schaal et al, 2014), French (Degrave & Dedonder, 2019), Portuguese (Lima et al, 2020), traditional Chinese (Lin et al, 2021), Japanese (Sadakata et al, 2022), Danish, and Russian (both language versions are available at https://shiny.gold-msi.org/gmsiconfigurator/). As such, it could stimulate future work within and across research communities and encourage the emergence of more cross-cultural research.…”
Section: From Musicality To Musical Sophisticationmentioning
confidence: 99%
“…Furthermore, while this definition of musical sophistication was posited by European researchers in a Western cultural context, their notions of musical engagement—including the nature of performing skills—are general enough to apply to all contexts in which they have been currently tested. Examples of these contexts include the original study that was open to participants from all over the world (although primarily completed by participants in the United Kingdom, United States, Canada, and Australia; Müllensiefen et al, 2014), collegiate students in the United States (Baker et al, 2020), older American adults (Petrovsky et al, 2017), a French translation validated in Belgium and France (Degrave & Dedonder, 2019), a Portuguese translation validated in Portugal (Lima et al, 2018), a Chinese translation validated in Taiwan (Lin et al, 2019), a German translation validated in Germany (Schaal et al, 2014), and a Japanese translation validated among native Japanese speakers (Sadakata et al, 2022). As evidenced by the many citations of Gold-MSI (Google Scholar shows that Müllensiefen et al, 2014, has been cited 801 times as of this writing, while Web of Science, a global citation database, reports this article to be in the top 1% of articles cited in the psychiatry/psychology field, with over 329 articles referencing it), this measure of musicality has become popular among researchers.…”
Section: Measuring Musicalitymentioning
confidence: 99%